ANALISIS PENERAPAN PELAPORAN KEUANGAN ENTITAS NIRLABA BERDASARKAN PSAK NO. 45 PADA MASJID DI KOTA BANDA - Nazila, Siti Rahma; Fahlevi, heru (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The purpose of this research is to determine the financial statements of mosques in the city of Banda Aceh in compatible with PSAK No. 45 and the quality of the financial report system of mosques in Banda Aceh. The type of research used in this study is descriptive quantitative method with Probability sampling which is using cluster random sampling. The data used in this study are primary data, namely a questionnaire distributed to 50 respondents from 25 mosques in Banda Aceh City. The questionnaire was distributed to the Head of BKM and Treasurer. The research data was obtained directly from the respondents by filling out the questionnaires that were distributed. The results of this study show that mosques in Banda Aceh City in general have not applied PSAK No. 45 concerning Nonprofit Financial Reporting because mosques do not have financial position reports, activity reports, cash flows, notes to financial statements. Mosques only make simple financial reports covering the sources of income, expenses, and cash balances at the end of the period and the obstacles that cause the mosque to not implement PSAK No. 45 namely the constraints of understanding in the preparation of mosque financial reports according to PSAK No. 45 and lack of human resources with accounting background.